Dentin contamination during repair procedures: A threat to universal adhesives? - Anne‐Katrin Lührs; Cosima Brachmann; Silke Jacker‐Guhr (Wiley, 2022)
Abstract Objective This study examined the influence of surface contamination during repair procedures with hydrofluoric acid, silane, or ammonium polyfluoride on the bond strength of universal adhesives to dentin using different etching modes before and after thermocycling. Materials and Methods Dentin surfaces of human molars were contaminated in different ways (silane, hydrofluoric acid, ammonium polyfluoride, and no pretreatment as control) followed by application of a universal adhesive (etch & rinse or self‐etch mode). After a composite build‐up was placed onto each tooth, sticks for the microtensile bond strength (MTBS) test were sectioned. Half of the sticks were tested after water storage for 24 h, the other half after thermocycling (15,000 cycles, 5/55°C). The MTBS data were analyzed statistically by using the Kolmogorov-Smirnov test, one‐way analysis of variance, and Tukey HSD test (p < 0.05). The fracture patterns of all specimens were evaluated and analyzed using a χ2 test. Results Dentin contamination with a multifunctional silane does not influence microtensile bond strength irrespective of aging. Contamination with hydrofluoric acid or an ammonium polyfluoride primer leads to a significantly lower bond strength after aging, irrespective of the etch mode. Conclusion Dentin contamination with hydrofluoric acid or ammonium polyfluorides during repair procedures should be avoided, as they appear to decrease the bond strength of universal adhesives.